A summary of Blastocystis subtypes in North and South America (2019)
Background: Blastocystis is a stramenopile of worldwide significance due to its capacity to colonize several hosts. Based on its high level of genetic diversity, Blastocystis is classified into global ribosomal subtypes (STs). The aim of this study was to conduct a summary of Blastocystis STs and depict their distribution throughout North and South America; we did this by assembling maps and identifying its most common 18S alleles based on diverse studies that had been reported all over the continent and whose Blastocystis-positive samples were obtained from numerous hosts. Results: Thirty-nine articles relating to nine countries from the American continent were considered, revealing that ST1 (33.3%), ST2 (21.9%), ST3 (37.9%), ST4 (1.7%), ST5 (0.4%), ST6 (1.2%), ST7 (1%), ST8 (0.7%), ST9 (0.4%), ST12 (0.3%), Novel ST (1.1%) and Mixed STs (0.2%) occurred in humans. The STs in other animal hosts were ST1 (6.5%), ST2 (6.5%), ST3 (4.7%), ST4 (7.2%), ST5 (15.9%), ST6 (17.3%), ST7 (3.6%), ST8 (20.6%), ST10 (9%), ST14 (3.6%), ST17 (1.1%) and Novel ST (4%). The countries that presented the most abundant variety of studies reporting STs were the USA with 14 STs, Brazil with 9 STs and Colombia with 8 STs. Additionally, new variants had been described in the last few years, which have increased the prevalence of these subtypes in the countries studied, such as Novel ST (1.1%) and Mixed STs (0.2%) in humans and Novel ST (4%) in animals. Conclusions: This summary updates the epidemiological situation on the distribution of Blastocystis STs in North and South America and will augment current knowledge on the prevalence and genetic diversity of this protozoan. © 2019 The Author(s).